Красный камень: повести / Н. Н. Шпанов - Шпанов Николай Николаевич (Военные приключения, 2010)
Экземпляры: аб. (2020) / Инвентарный номер: 56013 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Ш 83 / ББК: 84(2=411.2)6